Readings in economics of forestry, energy and environment in Malaysia - Abdul Rahim, Khalid; Mohd Noh, Kusairi (Universiti Putra Malaysia Press, 2014)
This book on “Readings in the Economics of Forestry, Energy, and Environment in Malaysia” has a special emphasis on the problems and concerns of developing countries, especially Malaysia in the international and sustainable development debates. It seeks to find those areas of synergy where forest economics, energy economics and environmental economics can be mutually beneficial for decisions towards sustainable development, and to help policy makers exploit those opportunities. It seeks to identify areas of conflict among the three policy spheres, and help find ways to minimize them. And it also seeks to increase civil society’s understanding of the issues, and create mechanisms of openness which can help make a better policy.